Comparison of weed control methods on infestation and crop productivity in transplant aman rice - Hasan, MN; Sarker, UK; Uddin, MR; Hasan, AK; Kaysar, MS (Progressive Agriculture, 2017)
An experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh during the period from June to December 2014 with a view to compare the efficacy of weeding method on the performance of transplanted aman rice varieties. Four transplanted aman rice varieties viz. Kalijira, BRRI dhan34, BRRI dhan52 and BRRI dhan64 and five different weeding treatments namely no weeding, two hand weeding at 20 & 40 days after transplanting (DAT), mechanical weeding by Japanese rice weeder at 20 and 40 DAT, soil applied pre-emergence herbicide Topstar 400 SP (Oxadiargyl 400 g/l) @ 190 ml ha-1 once at 3 days before transplanting and foliar applied post-emergence herbicide Manage @ 250g ha-1 at 6 days after transplanting were evaluated. The experiment was laid out in a split plot design assigning weed control method in the main plot and variety in the sub plot with three replications. Weed population was significantly influenced by variety and methods of weeding. The important weeds of the experimental plots were Digitaria sanguinalis, Leersia hexandra, Paspalum scrobiculatum, Echinochloa crusgalli, Monochoria vaginalis, Ludwigia hyssopifolia, Polygonum orientale, Eclipta alba, Marsilea crenata and Fimbristylis miliacea. The effect of weeding treatments on dry weight of weeds was significant. Hand weeding at 20 and 40 DAT showed the lowest dry weight of weeds followed by post-emergence herbicide Manage at 6 DAT and no weeding produced the highest dry weight of weeds. Among the weeding treatments hand weeding at 20 and 40 DAT performed the best for all the crop characters including grain yield (3.90 t ha-1) followed by the post-emergence herbicide manage and no weeding showed the lowest performance (3.06 t ha-1). Among the varieties, BRRI dhan34 produced the highest grain yield (4.33 t ha-1) and Kalijira yielded the lowest (2.04 t ha-1). The interaction between variety and weeding show that all the varieties produced higher grain yield with two hand weeding at 20 and 40 DAT than other weeding treatments. The results suggested that BRRI dhan34 might be grown with two hand weeding at 20 and 40 DAT as well as early post-emergence herbicide Manage for effective in controlling weeds and for better yield of transplant aman rice. Progressive Agriculture 27 (4): 418-427, 2016